THE CONCEPT OF OFFICE COMMUNICATION IN ISLAMIC PERSPECTIVE - wahyuni, kurnia; Diana Suci Wulandari; Harahap, Nasrun (International Journal of Multidisciplinary Reseach, 2025)
Communication has a crucial role in human life. Through effective communication, harmonious relationships between individuals can be created, considering that humans are essentially social creatures who need interaction with each other. This study aims to explain the concept of office communication, including understanding, elements, forms, and communication in an Islamic perspective. The method used is qualitative with a literature study approach. Data were collected through literature analysis from various books and journal articles relevant to the research topic. The results showed that office communication is a process that starts from processing ideas, transforming data into information, to delivering messages by the authorities to the parties in need. This process utilizes various office communication media so that messages can be conveyed effectively to achieve organizational goals. From the Qur'anic perspective, forms of communication emphasize the importance of speaking with honesty, gentleness, and effectiveness. Principles such as correct speech (qaulan sadidan), easy to understand (qaulan maysura), good (qaulan ma'rufan), effective (qaulan balighan), noble (qaulan kariman), and gentle (qaulan layyinan) are used as guidelines.